2009
DOI: 10.1017/s0960258509301099
|View full text |Cite
|
Sign up to set email alerts
|

Role of the lens in controlling water uptake in seeds of twoFabaceae(Papilionoideae) species treated with sulphuric acid and hot water

Abstract: Although many studies have been conducted on seeds with a water-impermeable seed or fruit coat (physical dormancy), the primary site of water entry into these seeds after dormancy-breaking treatments is still controversial. Thus, the role of lens, hilum, micropyle and extrahilar regions in water uptake of seeds treated to break physical dormancy was examined inVigna oblongifoliaandSesbania sesban(Fabaceae) following pretreatment with sulphuric acid and hot water. Morphology of seed surfaces in treated versus n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 21 publications
3
48
0
6
Order By: Relevance
“…This could be explained by the fact that the hilum and the lens are also involved in water absorption, but participate less than the micropyle at the beginning of imbibition, as proposed by Tailor (2005) for physically dormant Fabaceae seeds from Australian pastures. Difference in water uptake between different water gap has been also noted by Hu, Wang, Wu, Nan, and Baskin (2008) and Hu, Wang,Wu, and Baskin (2009). An interesting aspect of water imbibition observed in the present work, and already observed by Hu et al (2008) and Hut et al (2009), was the evidence that the water inlet region can be different between initial and subsequent soaking days.…”
Section: Discussionsupporting
confidence: 88%
“…This could be explained by the fact that the hilum and the lens are also involved in water absorption, but participate less than the micropyle at the beginning of imbibition, as proposed by Tailor (2005) for physically dormant Fabaceae seeds from Australian pastures. Difference in water uptake between different water gap has been also noted by Hu, Wang, Wu, Nan, and Baskin (2008) and Hu, Wang,Wu, and Baskin (2009). An interesting aspect of water imbibition observed in the present work, and already observed by Hu et al (2008) and Hut et al (2009), was the evidence that the water inlet region can be different between initial and subsequent soaking days.…”
Section: Discussionsupporting
confidence: 88%
“…As indicated before, storage of white lupin seeds at −20 ∘ C for a period of time or immersing the seeds in liquid nitrogen was not sufficient to meet a need for practical application suggesting that combining freezing temperature with HW at given conditions provided a surface stress on seed coat which can easily be broken and made seeds permeable to water. Previous reports indicated that lens or hilum sides of the testa are the physically weakest part and thus can more easily be broken by treatments [6,23,53]. We speculate that the F1 + HW method may also provide cracks on lens or hilum sides of the testa on white lupin and red clover seeds.…”
Section: Discussionmentioning
confidence: 74%
“…It has been suggested that cracks in the seed coat produced by heat treatment result from seed coat expansion and contraction due to the increase of room temperature to −80 ∘ C (hot water) [23,53] while cracks in acid-scarified seeds may be attributed to chemical erosion. The F1 + HW method provides cracks on seed coat and results may be attributed to seed coat expansion or contraction due to the heat shocked on testa of frozen seed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em sementes de Sesbania sesban e Vigna oblongifolia (Fabaceae), Hu et al (2009) verificaram que o principal local de entrada de água nas sementes após a quebra de dormência física pode variar de acordo com os tratamentos utilizados, o que pode determinar a velocidade da absorção de água, e subsequente germinação.…”
Section: Figura 3 Emergência (A) íNdice De Velocidade De Emergênciaunclassified